2013
DOI: 10.1016/j.yebeh.2013.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant and anticonvulsant effects of exercise in a rat model of epilepsy and depression comorbidity

Abstract: The bi-directional comorbidity between epilepsy and depression is associated with severe challenges for treatment efficacy and safety, often resulting in poor prognosis and outcome for the patient. We showed previously that rats selectively bred for depression-like behaviors (SwLo rats) also have increased limbic seizure susceptibility compared with their depression-resistant counterparts (SwHi rats). In this study, we examined the therapeutic efficacy of voluntary exercise in our animal model of epilepsy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 45 publications
5
20
1
5
Order By: Relevance
“…Moreover, the beneficial influence of aerobic training in a model of epilepsy and depression comorbidity has been recently documented (Epps et al, 2013). In the present study, we report for the first time that long-term aerobic exercise can alleviate the development of KA-induced SE, epileptogenesis and concomitant behavioral changes in hypertensive rats.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, the beneficial influence of aerobic training in a model of epilepsy and depression comorbidity has been recently documented (Epps et al, 2013). In the present study, we report for the first time that long-term aerobic exercise can alleviate the development of KA-induced SE, epileptogenesis and concomitant behavioral changes in hypertensive rats.…”
Section: Discussionsupporting
confidence: 62%
“…20 The present fi ndings are in agreement with Epps et al 20 and demonstrated that the benefi cial effect of exercise program is associated with other positive outcomes, including cardiovascular, depression and impulsive behavior in a rat model of co-morbid hypertension and epilepsy. чение каинатом через месяц тренировок облегчило ангедонию, вызванную эпилепсией при SРТ и соответственно стереотипное поведение при HBT.…”
Section: Resultssupporting
confidence: 92%
“…Ratas con depresión de la especie SwLo sometidas a actividad física se compararon con controles sin exposición al ejercicio. El primer grupo aminoró los síntomas negativos del ánimo y se demoró en desarrollar la epilepsia (78). Los investigadores relacionan los efectos positivos inducidos por el ejercicio con el incremento de la galanina.…”
Section: ¿Cómo Se Explica La Mejoría De La Comorbilidad Depresiva En unclassified